PEMBUATAN SKENARIO FILM œLEGENDA TANJUNG MENANGIS DARI NASKAH LONTAR CILINAYA: SEBUAH PROSES EKRANISASI - Widiyastantia, Eva Mawinda (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
AbstractOn the island of Lombok, one of the renowned ancient manuscripts both in presence and legend is the Cilinaya palm-leaf manuscript. Historically, the ancient lontar Cilinaya manuscript has only been kept in museums and held by traditional leaders to be read occasionally during cultural processions. This research deliberately made the script into a film scenario as a form of revitalization and cultural preservation that has the potential to continue to be developed. The objective of this endeavor is to create the film screenplay